Introduction to the Special Issue of the Canadian Journal of Counselling and Psychotherapy - Westwood, Marvin J.; Black, Tim G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Despite multicultural advances in the field, the counselling profession is arguably failing to meet the needs of men who endorse traditional masculine social ideology. This editorial provides the perspective of two practitioners who have worked extensively with traditionally socialized men, including Canadian military men who are thought to strongly exemplify prototypical male ideology. The limitations of a strictly “feminine nurturance”-based counsellor training model are presented. Further, suggestions for effectively engaging men in therapy, based upon 14 years of clinical experience with a military population, are presented.